ABUL ABBAS AS-SAFFAH PEMILIK GELAR AS-SAFFAH (MENELISIK ARTI PENTING AS-SAFFAH DALAM PEMERINTAHAN ABULABBAS) - Putri Puspa Dewi; Salmiwati Salmiwati (Adisam Publisher, 2025)
Abul Abbas as-Saffah was the first Caliph of the Abbasid dynasty. As-Saffah's caliphate lasted for only about four years. Abul Abbas was given the title of As-Saffah in recognition of his character and wisdom, which reflected generosity and justice. This research uses a library research approach to explore information about Abul Abbas as- Saffah. The results of this research show that Abul Abbas wanted to show the world that he was a strong leader who would not hesitate to use violence to maintain his power. Abul Abbas succeeded in destroying the Umayyad power and paved the way for the rise of the Abbasid dynasty. Abul Abbas not only asserted his identity as a people-oriented leader but also laid the foundation for the development of a more inclusive and progressive Abbasid dynasty in Islamic history.